Mario Santoro (1905-1998): a pioneer of Italian nipiology - Iorio, Silvia; Zurlini, Fabiola (Medicina Historica, 2023)
Background and aim: After his death in 1998, the biography of Mario Santoro was the subject of studies published with the aim of reconstructing the biography and bibliography of his scientific production. These studies, generally rather celebratory, do not allow to deduce the substantial contributions that Santoro has made in medicine in areas such as paediatrics and, more specifically, nipiology. Methods: The sources to reconstruct the original contributions of the scientific work of Santoro are the documents kept in the historical archive of Studio Firmano. An analysis was carried out on documentation on the years of Santoro’s medical training at the Universities of Rome and Padua, as well as from 1939 to 1952, in which his interest in nipiology developed. Correspondence with the main scholars of reference for nipiology represents a useful scientific tool in documenting the importance assumed in the national and regional context of the activities carried out by Santoro. Results: It is remarkable the discover of the unpublished letter from Ernesto Cacace, the founder of Nipiology (Naples, 11 September 1945) that takes on the importance of a scientific manifesto, illustrating in detail the pioneering nipiological work carried out in Fermo. Conclusions: Santoro founded the first Italian school of nipiological assistants, started in an Italian brephotrophy and supported, with a series of initiatives, the scientific development of the Marche regional section of the Italian Society of Nipiology, becoming a pioneer of the diffusion in Italy of the nipiology as a new experimental science.